Junior picture dictionary - Kelly, Miles (United Kingdom : Miles Kelly publishing Ltd, 2017)
PICTURE DICTIONARIES (CHILDREN'S / TEENAGE). Introducing a huge range of subjects in fascinating detail, Junior Picture Dictionary features an encyclopedic range of objects, each with clear annotation. Covering hundreds of topics, this book provides younger readers aged 5+ with a wealth of knowledge in an accessible format. Packed with realistic artwork and amazing diagrams, and with a comprehensive index for easy navigation, children will find Junior Picture Dictionary a rewarding way to expand their vocabulary and broaden their knowledge.
Location: 4D
Keywords: Reference book